Prevalence of sarcopenia in older Brazilians: a systematic review and meta-analysis - Bergamaschine Mata Diz, Juliano; Henschke, Nicholas (Geriatrics and gerontology international, 2017)
Aim Sarcopenia is the age-related loss of muscle mass and function that evolves into disability, loss of independence and death. In Brazil the number of older people is rapidly growing, resulting in an increased prevalence of chronic conditions associated with old age. As prevalence estimates provide essential information to policymakers when developing healthcare strategies, this systematic review and meta-analysis aimed to estimate the prevalence of sarcopenia in older Brazilians. Methods Electronic database searches and hand-searching in relevant journals and reference lists were carried out without language restriction. Studies that reported the prevalence of sarcopenia in Brazilians aged 60 years or older were considered for inclusion. Sarcopenia was defined as low muscle mass, low muscle function or low muscle mass and function. Meta-analysis was carried out using a random-effects model. Results A total of 31 studies were included pooling 9416 participants. The overall prevalence of sarcopenia in older Brazilians was 17.0% (95% CI 13.0-22.0). Sensitivity analysis showed rates of 20.0% (95% CI 11.0-32.0) in women and 12.0% (95% CI 9.0-16.0) in men. Prevalence was 16.0% (95% CI 12.0-23.0) based on low muscle mass and function; and 17.0% (95% CI 9.0-31.0) based only on low muscle mass. The difference between these two criteria was not significant (P = 0.96). Conclusions Sarcopenia is an emerging public health issue in Brazil. Attention should be paid to changes in prevalence rates over the next years because of the increase in the older population. Geriatr Gerontol Int 2017; 17: 5-16.